Impact of Green Entrepreneurial Orientation and Entrepreneurial Education on Green Entrepreneurial Intention Through Environmental Awareness - Soelaiman, Lydiawati; Sariutami, Celyn (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 2 Tahun 2024DO - 10.24843/MATRIK:JMBK.2024.v18.i02.p01, 2024)
Indonesian Government has been planning the green economic strategy as an effort to prioritize the environmental sustainability. Green entrepreneurship aligns with this strategy by promoting environmentally-friendly business concept. This research aimed to reveal the effect of green entrepreneurial orientation and entrepreneurial education on green entrepreneurial intention in Jakarta, with environmental awareness as a mediator. Using descriptive quantitative approach, data was gathered through non-probability sampling method by using purposive-sampling technique from 269 young respondents in Jakarta through questionnaires. Data analysis was conducted by using SEM-PLS with the assistance of SmartPLS software version 4. The results show that entrepreneurial education has a significant effect on green entrepreneurial intention, but green entrepreneurial orientation does not significantly affect green entrepreneurial intention in Jakarta. Nevertheless, the effect of green entrepreneurial orientation on green entrepreneurial intention can be fully - mediated by environmental awareness. Keywords : entrepreneurial education; environmental ewareness; green economy; green entrepreneurial orientation; green entrepreneurial intention